The Early Days of NK Cells: An Example of How a Phenomenon Led to Detection of a Novel Immune Receptor System – Lessons from a Rat Model - Rolstad, Bent (Frontiers in Immunology, 2014)
In this review, I summarize some of the early research on NK cell biology and function that led to the discovery of a totally new receptor system for polymorphic MHC class I molecules. That NK cells both could recognize and kill tumor cells but also normal hematopoietic cells through expression of MHC class I molecules found a unifying explanation in the “missing self” hypothesis. This initiated a whole new area of leukocyte receptor research. The common underlying mechanism was that NK cells expressed receptors that were inhibited by recognition of unmodified “self” MHC-I molecules. This could explain both the killing of tumor cells with poor expression of MHC-I molecules and hybrid resistance, i.e., that F1 hybrid mice sometimes could reject parental bone marrow cells. However, a contrasting phenomenon termed allogeneic lymphocyte cytotoxicity in rats gave strong evidence that some of these receptors were activated rather than inhibited by recognition of polymorphic MHC-I. This was soon followed by molecular identification of both inhibitory and stimulatory Ly49 receptors in mice and rats and killer cell immunoglobulin-like receptors in humans that could be either inhibited or activated when recognizing their cognate MHC-I ligand. Since most of these receptors now have been molecularly characterized, their ligands and the intracellular pathways leading to activation or inhibition identified, we still lack a more complete understanding of how the repertoire of activating and inhibitory receptors is formed and how interactions between these receptors for MHC-I molecules on a single NK cell are integrated to generate a productive immune response. Although several NK receptor systems have been characterized that recognize MHC-I or MHC-like molecules, I here concentrate on the repertoires of NK receptors encoded by the natural killer cell gene complex and designed to recognize polymorphic MHC-I molecules in rodents, i.e., Ly49 (KLRA) receptors.